Enzymes, Biocatalysis and Chemical Biology - Serra, Stefano (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book provides recent studies focused on chemical biology and biocatalysis applied to organic synthesis. The articles range from topics such as fungal metabolism and fungi-mediated biotransformations to the exploitation of specific enzymes in biocatalyzed reactions, also including works on the characterization of enzymes and the study of their catalytic activity. Overall, ten studies are presented that provide the reader with relevant, fresh insights on the use of enzymes and on the importance of biocatalysis.